The Influence of Reference Group on Purchase Decision of Iphone Products With Lifestyle as A Moderating Variable (Case Study: Iphone Product Users In Indonesia) - Ahmad Darajat Basallama; Maya Ariyanti (Jurnal Manajemen Indonesia, 2023)
Indonesia is one of the countries with a significant market share. Based on data, it shows that Iphone market share in Indonesia is not among the top 5 biggest sales, especially with the current pandemic conditions. This problem occurs because other brands in the top rank also have variants of products that have similar to or the same prices as Iphone products. This research aims to determine the influence of reference groups on Iphone product purchasing decisions, the influence of lifestyle on Iphone product purchasing decisions, and the moderating effect of lifestyle on the relationship between reference groups and Iphone product purchasing decisions. The population of this research is Iphone users in big cities in Indonesia, namely Jakarta, Bandung, Bali, Medan, Pontianak, Makassar, Palembang, Lampung, and Ambon. The sampling technique used was cluster random sampling with a total sample of 150 respondents. The data collection method is a survey with an online questionnaire. The multivariate analysis was used in this research, namely structural equation modelling. The results of the study indicate that the reference group has a significant influence on Iphone product purchasing decisions, lifestyle has a significant influence on Iphone product purchase decisions, and lifestyle can moderate the positive relationship between reference groups and purchasing decisions. In future research, other sampling techniques and a more varied number of samples are expected to be used to obtain more comprehensive results. Keywords— Reference Group; Lifestyle; Purchase decision; Structural Equation Modelling.